(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVE: Decision-making capacity (DMC) is an indispensable prerequisite for patients’ informed consent and therefore directly related to the right to self-determination. In view of this ethical implication, valid and reliable assessment of DMC is essential to best practice. In general, and with particular regard to the Swiss context, little is known about healthcare practitioners’ knowledge of and attitudes to the concept of DMC, or about their assessment practice. The present study aims to close this gap. METHOD: A randomised representative sample of 3,500 physicians, including all specialisms and from all parts of Switzerland, were contacted by mail and invited to complete a survey questionnaire, which was specifically designed for the purpose of the study. RESULTS: A total of 763 questionnaires were included for analysis (response rate: 22.15%). Physicians diverged in their general understanding of DMC as either a dichotomous or a gradual concept, and in relation to the conceptual challenges of decisional relativityand risk-relativity. Along with cognitive abilities, emotional, intuitive, or evaluative factors were acknowledged as important criteria. DMC was most often assessed implicitly: explicit assessments, if conducted, depended mainly on unstructured interviews. A discrepancy was identified between physicians’ perceptions of responsibility and qualification, indicating a related need for more guidance and training. CONCLUSION: The conceptual and practical challenges of DMC are far from being resolved. There is a clear need for more guidance in this area in the form of guidelines, tools, and training.